KETERAMPILAN KEPEMIMPINAN PENGUSAHA INDUSTRI SKALA KECIL (STUDI DI BANDAR LAMPUNG) - Hayati, Keumala; Sari, Aida (Journal of Indonesian Economy and Business, 2007)
This research is focused on management in small-scale industries in BandarLampung seen from entrepreneursâ leadership aspect consisting of technical,interpersonal, and conceptual skills. The success of management in the industries isinseparable from the leadership skills. Without these skills, it is anxious that graduallythe industries might develop slowly and be difficult to adapt to the change anddevelopment of their environment.This research is aimed at finding out leadership skills of the entrepreneurs insmall-scale industries reflected in the employeesâ performance, satisfaction andcommitment to the industries. The analysis unit was at small-scale processing industriesin Bandar Lampung. The number of the samples was 63 units consisting of 26 foodindustries, 16 printing industries, and 21 furniture industries. The assessment ofleadership skills and their influence on employeesâ performance, satisfaction andcommitment was performed by giving questionnaires to the 371 employees. Thestandards used in the questionnaires were semantic differential scale and analysis toolusing Structural Equation Modeling (SEM) with software Lisrel 8.30.The research result shows that the leadership skills comprising technical,interpersonal and conceptual skills collectively influenced the employeesâ performance,satisfaction and commitment to the industries. While, individually, this can be seen asfollows: 1) technical skill did not significantly influence their performance, satisfactionand commitment to the industries; 2) interpersonal skill significantly influenced theirperformance and satisfaction, except commitment; 3) conceptual skill significantlyinfluenced their performance and commitment, except satisfaction. Furthermore, it wasfound that the employeesâ performance in small-scale industries in Bandar Lampungdid not significantly influence their commitment, but their satisfaction significantlyinfluenced their commitment to the industries. It also was found that the employeesâsatisfaction significantly influenced their performance.Keywords: Leadership skills: technical skill, interpersonal skill, conceptual skill,Â Employeesâ performance, satisfaction, commitment, small-scaleindustries in Bandar Lampung.